Reflections and experiences of mentors, tutors and writing consultants on enhancing student Learning during the COVID-19 pandemic - Ravhuhali, F.; Tshililo, T. Y.; Mboweni, H. F.; Muthivhi, K. M. (South African Journal of Higher Education, 2024)
The experiences of mentors, tutors, and writing consultants in the execution of their roles during unprecedented times, particularly the COVID-19 pandemic, remain insufficiently explored and inadequately documented. This article, which adopts a qualitative research methodology with a specific focus on a rural-based comprehensive university in South Africa, delves into the experiences and reflections of mentors, tutors, and writing consultants in the course of their duties during the COVID-19 pandemic. We contend that providing safe spaces for mentors, tutors and writing practitioners to share their experiences on their roles not only during the pandemic should be central to all student support initiatives. This fosters a sense of reflection on their practices which in turn results in professional growth and development as reflective practitioners capable of enhancing student success in higher education. In assessing their work, data was gathered from a population comprising seventy-two selected mentors and tutors (referred to as MenTuts), as well as writing consultants affiliated with the Academic Development Unit (ADU) of the institution. Content and thematic analysis were employed to examine the data after coding. The reflections and experiences of MenTuts and writing consultants were both positive and negative. They expressed enthusiasm for their roles during the COVID-19 pandemic but also conveyed feelings of being overwhelmed by the challenges they faced. This underscores the need for exploring alternative approaches to mentoring, tutoring, and writing consultancy to enhance effective student learning and success in higher education during both present and future unprecedented times. Given the plethora of recent unprecedented events, higher education institutions in South Africa as well as in Africa should start undertaking innovative radical approaches for student support initiatives that are centred around engaging with mentors, tutors, and writing consultants to ensure that they are able to reflect on their experiences to enhance student learning.